Analisis Kemampuan Literasi Numerasi dalam Menyelesaikan Soal Cerita Melalui Media PACAPI Kelas II SDN Karangrejo 02 Semarang - Utami, Desi Tri; Artharina, Filia Prima; Sumarmiyati, Sumarmiyati; Patonah, Siti (LPPM Institut Pendidikan Nusantara Global, 2024)
Mathematical literacy needs to be developed since elementary school. This is important to ensure that the next generation is ready to solve problems in all aspects of life. However, in reality, students' literacy skills are not as expected. Based on the results of interviews with class II teachers of SDN Karangrejo 02 Semarang, many students were found to have difficulties in the learning process, especially mathematics in the material of fractions in the form of story problems. The purpose of this study was to analyze the ability of numeracy literacy in solving story problems through the PACAPI media of class II SDN Karanggrejo 02 Semarang. The method used in this study used a qualitative descriptive method. In its implementation, it used observation, test, and interview guidelines. The research sample was all 17 class II students. The results of this study indicate that teachers are advised to train students more often by giving questions that lead to numeracy literacy skills and increasing the level of math problems that will be given to students. The instillation of the concept of fractional arithmetic operations also needs to be emphasized again to students so that students can solve math problems correctly.